2021
DOI: 10.1177/2040622321990262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long head of the biceps tendon histopathology and long-term functional results in smokers. A time to reevaluate the Bonar score?

Abstract: Aim: The purpose of this study was to investigate whether there is an association between smoking, the extent of the degeneration process in the biceps tendinopathy, including cells and extracellular matrix (ECM) alterations, and long-term surgical results. Methods: This study comprised 40 consecutive patients admitted for shoulder arthroscopy due to symptomatic biceps tendinopathy and classified into three groups based on smoking status: active smokers, former smokers, and non-smokers. According to the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…These results should be taken with caution. Indeed, a recent study has discussed the vascularity subclass index of the Bonar score which may not be well adapted to tendinopathy and could be revised [ 32 ]. Furthermore, neovascularization in tendinopathy is a complex process implicated in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…These results should be taken with caution. Indeed, a recent study has discussed the vascularity subclass index of the Bonar score which may not be well adapted to tendinopathy and could be revised [ 32 ]. Furthermore, neovascularization in tendinopathy is a complex process implicated in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified on average only moderate histopathological changes, uniformly distributed according to the Bonar score (9.1 ± 2.3) despite the analysis of the entire LHBT. Fearon et al suggest to use the area of the tendon with the worst histopathological Bonar score in order to identify the worst degree of tendinopathy and use this section’s score for representative purposes despite that, we and similarly, Zabrzynski et al did not identify any correlation of the histopathological changes of the LHBT by the Bonar score and clinical outcomes [ 30 ]. The LHBT is a unique tendon as its main portion is located intraarticularly and therefore the tendon histology can be different to other, particularly extraarticular, tendons of the body.…”
Section: Discussionmentioning
confidence: 99%
“…The neovascularization process is crucial in biceps tendinopathy and was significantly reduced in patients with smoking history. Furthermore, the morphological alterations of rotator cuff tendons also correlated positively with the extent of biceps tendon degeneration [ 30 , 31 ]. These studies indicated the influence of RCT on the structural and biochemical changes in LHBT.…”
Section: Discussionmentioning
confidence: 99%